Design and experiment of landslide monitoring algorithm based on MEMS sensor - Di WU; Taiming LIANG; Jing WU; Jianjian WU; Yang YI; Wanpeng LOU (地质科技通报)
Objective To address current engineering challenges such as poor stability and accuracy, limited coverage, and high costs associated with soil landslide displacement monitoring, a novel method based on microelectromechanical system (MEMS) sensor technology is proposed. Methods By considering the kinematic characteristics of slope deformation, a time-domain acceleration integration algorithm is designed to correct random and systematic errors in the acceleration data collected by MEMS sensor. To verify the effectiveness and practicality of this displacement monitoring method, two indoor landslide model tests and corresponding finite element simulation calculations were designed and conducted. MEMS technology was used to monitor the internal displacement of the soil for the test slopes, and the results were compared with the the finite element simulation outputs to evaluate the accuracy and reliability of the algorithm. Results The findings indicate that the MEMS-based soil landslide displacement monitoring achieved a minimum average relative error of 0.09% in the horizontal direction and 0.50% in the vertical direction, demonstrating high accuracy and suitability for practical engineering applications. Conclusion The research results provide a novel approach to soil landslide monitoring and provides a theoretical foundation for the integrating MEMS sensors in landslide and slope safety engineering.